Spherical Principal Series of Quantum Harish-Chandra Modules - Bershtein, O.; Stolin, A.; Vaksman, L. (Журнал математичної фізики, аналізу, геометрії, 2007)
The nondegenerate spherical principal series of quantum Harish-Chandra modules is constructed. These modules appear in the theory of quantum bounded symmetric domains.Mathematics Subject Classification: 17B37, 22E45